Optimalisasi Daya Mesin Diesel Common Rail - Ridwan Djohari (KILAT, 2020)
This research aims is to increase engine power by raising the air temperature and fuel temperature into the engine and its effect on the resulting of SFC. Diesel engines that are use turbocharger, the air temperatures have increased but the fuel temperature is still fixed. The problem is how if the air temperature and fuel temperature are raised whether the engine power will increase and the SFC will change. This study was conducted with experiments using a car that the air temperature is adjusted up to 100oC and the fuel temperature that goes into the engine is made a maximum of 70oC. The test results show that with rising air temperatures and fuel temperatures going into the average power engine will raise and save fuel, power and saving SFC occurs at 90°C and 70oC fuel. Rotation of engine that can produce power and fuel-efficient is at around 2000 rpm.